Impact of behavioural risk factors on death within 10 years for women and men in their 70s: absolute risk charts - Dobson Annette; McLaughlin Deirdre; Almeida Osvaldo; Brown Wendy; Byles Julie; Flicker Leon; Leung Janni; Lopez Derrick; McCaul Kieran; Hankey Graeme J (BMC, 2012)
Abstract Background Estimates of the absolute risk of death based on the combined effects of sex, age and health behaviours are scarce for elderly people. The aim of this paper is to calculate population based estimates and display them using simple charts that may be useful communication tools for public health authorities, health care providers and policy makers. Methods Data were drawn from two concurrent prospective observational cohort studies of community-based older Australian women (N = 7,438) and men (N = 6,053) aged 71 to 79. The outcome measure was death within ten years. The predictor variables were: sex, age, smoking status, alcohol consumption, body mass index and physical activity. Results Patterns of risks were similar in men and women but absolute risk of death was between 9 percentage points higher in men (17 %) than in women (8 %) in the lowest risk group (aged 71-73 years, never smoked, overweight, physically active and consumed alcohol weekly) and 21 % higher in men (73-74 %) than women (51-52 %) in the highest risk group (aged 77-79 years, normal weight or obese, current smoker, physically inactive and drink alcohol less than weekly). Conclusions These absolute risk charts provide a tool for understanding the combined effects of behavioural risk factors for death among older people.